The Effect of Profit Sharing System, Religiosity and Ease of Using Digital Banking on Interest in Using Islamic Banks in Bekasi - Ari Sulistyowati; Choiroel Woestho; Adi Wibowo Noor Fikri (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study is to determine the Effect of Profit Sharing System, Religiosity and Ease of Using Digital Banking on Interest in Using Islamic Banks in Bekasi. This study uses a descriptive quantitative research method in which users of Islamic Banks in Bekasi become the object. This study used a purposive sampling technique and used a sample of 70 respondents. The design used in this study is hypothesis testing using a structural equitation model (SEM) – SmartPLS 4.0. The results of this study indicate that 2 X variables consisting of Religiosity and ease of using digital banking have an influence on interest in using Islamic banks in Bekasi. Meanwhile, the System Profit Sharing variable has no influence on the interest in using Islamic banks in Bekasi. This study has a limited object of research that only uses 70 respondents who use Islamic banks in Bekasi as research respondents. This is used as a suggestion for future researchers. The novelty in this study combines the variables of System Profit Sharing, Religiosity and Ease of Using Digital Banking on Interest in Using Islamic Banks in Bekasi.